Numerical simulations of isothermal solidification process - Jojin, Siniša; Kovač, Risto (Journal of Production Engineering, 1990)
A solution of mathematical model of solidification of a casting is presented. The explicit method of finite diferences is used for determination of temperature distribution across the well of the casting and the system casting-mould. Numerical calculations took in account nonlinearityes, like changing of material properties of the casting (conductivity and specific heat capacity) as a functions of temperature, and changing of the interfacial heat transfer coeficient between casting and the mould within time. Apart from that, during the time of cooling of liquid material, what is the first period, convection is taken in account by using efectiv value of conductivity for ligquid state. The calculated results are compared with experimental mesurements for solidification of aluminium. It is the example for isothermal solidification. The results are presented in the form of cooling curves in the most caracteristics points of the system casting--mould like they are: midle of the casting, surface of the casting, out and iner surface of the wall of mould (die).